(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article deals with the theatrical and dramaturgic activities of Vasily Hogol-Yanovsky who was the head of D. Troshchinsky home theatre in Poltava region. He created his plays «Prostak» and «Sobaka-vivcya» in the beginning of the XIX th century. It is defined in the article that having created these plays the playwright became the pioneer of the Ukrainian serious comedy.